Tito : A Biography - Auty, Phyllis (London Longman group Limited, 1970)
A biography of the Croatian peasant who rose to become leader of the Yugoslav Communist Party and President of Yugoslavia.
Include Notes, Bibliography and Index
Keywords: Tito, Josip Broz, 1892-1980 -- Yugoslavia